Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s13364-011-0038-9
|View full text |Cite
|
Sign up to set email alerts
|

Density of tiger and leopard in a tropical deciduous forest of Mudumalai Tiger Reserve, southern India, as estimated using photographic capture–recapture sampling

Abstract: Density of tiger Panthera tigris and leopard Panthera pardus was estimated using photographic capturerecapture sampling in a tropical deciduous forest of Mudumalai Tiger Reserve, southern India, from November 2008 to February 2009. A total of 2,000 camera trap nights for 100 days yielded 19 tigers and 29 leopards within an intensive sampling area of 107 km 2 . Population size of tiger from closed population estimator model M b Zippin was 19 tigers (SE=±0.9) and for leopards M h Jackknife estimated 53 (SE=±11) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 26 publications
1
53
1
Order By: Relevance
“…Using an ad hoc buffer, the ½MMDM method resulted in a much higher estimation of serval density than the maximum-likelihood SECR and Bayesian SECR models, whereas the full MMDM density estimate was similar and not statistically different from either of the SECR density estimates. Given the uncertainties of using an ad hoc buffer, these SECR methods are ideal for the study of rare species (Obbard et al 2010;Kalle et al 2011;Gerber et al 2012). Hence we suggest considering SECR model estimates for conservation decision making.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using an ad hoc buffer, the ½MMDM method resulted in a much higher estimation of serval density than the maximum-likelihood SECR and Bayesian SECR models, whereas the full MMDM density estimate was similar and not statistically different from either of the SECR density estimates. Given the uncertainties of using an ad hoc buffer, these SECR methods are ideal for the study of rare species (Obbard et al 2010;Kalle et al 2011;Gerber et al 2012). Hence we suggest considering SECR model estimates for conservation decision making.…”
Section: Discussionmentioning
confidence: 99%
“…We generated systematic home range centers in an area contained within a 5-km buffer, which was larger than the mean maximum distance moved around camera traps. The large buffer around the sampled area ensured inclusion of home ranges of individuals exposed to cameras (Royle and Dorazio 2008;Kalle et al 2011). Detailed description of all methods can be viewed elsewhere (Karanth 1995;Karanth and Nichols 1998;Efford et al 2004;Efford 2009;Royle et al 2009;Ramesh 2010;Ramesh et al 2012b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The density was 1.31 (SE 0.32) and 0.87 (SE 0.28) tigers/100 km 2 from ½ MMDM and MMDM of Program DENSITY (Table 1). The density from Spatial Explicit Capture-recapture of Maximum likelihood provided 0.61(SE 0.15) For density analysis, the likelihood approach (Efford et al, 2004) seems to be appropriate being comparatively less sensitive to buffer width as it is directly based on parameters estimating density unlike Bayesian and is faster, and both spatial methods (Royle et al, 2009) have not shown any significant difference in terms of density estimation (Kalle et al, 2011). Thus, the likelihood approach was interpreted for discussion.…”
Section: Tiger Abundancementioning
confidence: 99%